Effect of Service Quality and Patient Satisfaction on Behavioral Intention - Wayan Karsana; Werner Ria Murhadi (Program MM Universitas Surabaya, 2021)
Service quality is an essential aspect in realizing patient satisfaction and behavioral intention in the health service industry. The behavioral intention has been identified as an essential construct in measuring organizational success and affects patient visits. This study aims to determine service quality and patient satisfaction on behavioral intention in the Husada Utama Hospital. This study was quantitative causal research to determine the effect of two or more variables. Primary data collected with a questionnaire include the perceived service quality scale, patient satisfaction scale, and behavioral intention scale. This study's sample was 150 respondents; consist of inpatients room for class 1, 2, and 3 that met inclusion criteria. The sampling method for this study was purposive sampling. Data analyzed using SEM AMOS to analyze measurement model, structural model, and hypothesis test. This study found that: service quality has a significant positive effect on patient satisfaction, service quality has a significant positive effect on behavioral intention, and there was no positive effect of patient satisfaction on behavioral intention. Service quality has a positive effect on behavioral intention, so patients' increasing behavioral intention can be done by improving the service quality. Further research needs to be conducted to analyze the effect of service quality on the behavioral intention with patient's satisfaction as a mediator; further research also needs to develop a patient's behavioral intention enhancement program.